Accuracy, Reproducibility and User Experience With Standardized Instructions for Measurement of Total Kidney Volume in Autosomal Dominant Polycystic Kidney Disease. Issue 2 (May 2023) - Bevilacqua, Micheli; Hague, Cameron J.; Romann, Alexandra; Levin, Adeera
Purpose: Total kidney volume (TKV) measurement is integral in clinical management of autosomal dominant polycystic kidney disease (ADPKD) but the gold standard of measurement via stereology/manual planimetry is time-consuming and not readily available to clinicians. This study assessed whether standardized measurement instructions based on an ellipsoid equation enhanced TKV assessment on computed tomographic (CT) images of the kidneys as determined by accuracy, reproducibility, efficiency and/or user acceptability. Methods: Participating radiologists were randomized to perform TKV measurements with or without standardized instructions. All participants measured the same 3 non-contrast, low-dose CT scans. Accuracy was assessed as variation from TKV measurements obtained by planimetry. Intraclass correlation coefficients and time to complete the measurements were assessed. Surveys assessed prior experience with TKV measurement and user acceptability of the instructions. Results: 49 radiologists participated. There was no difference in accuracy or measurement time between instructed and non-instructed participants. There was a trend towards greater reproducibility with standardized instructions (ICC .8 vs .6). 92% of respondents indicated the instructions were easy to use, 86% agreed the instructions would enhance their comfort with TKV measurement and 75% agreed they would recommend these instructions to colleagues. Conclusions: Instructed and non-instructed participants demonstrated similar accuracy and time required for TKV measurement, but instructed participants had a trend towards greater reproducibility. There was high acceptability including enhanced user confidence with the instructions. Standardized instructions may be of value for radiologists seeking to improve their confidence in providing clinicians with TKV measurements necessary to appropriately manage this patient population.